Analisis Faktor-Faktor Yang Mempengaruhi Keputusan konusmen Dalam Melakukan Pinjaman Pada KSU Jati Diri SIMO Boyolali - Handayani, Rumyani; Nurtantiono, Andri (Graduasi: Jurnal Bisnis & Ekonomi, 2013)
Intention of this research is : 1) To know reputation factor influence of company, loan procedure and level of service to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali. 2) To know factor having an effect on most dominant to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali.    Hypothesis  submitted  is  :  1)  Anticipated  there  is  influence  between  company reputations, loan procedure and level of service to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali; 2) Anticipated loan procedure factor to have influence very dominan to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali.    Population from this research is consumer (client) what does loan at KSU Jati Diri Simo Boyolali. Level of sample in this research 80 responders. Data source applied is  primary  data.  Data  collecting  technique  applied  is  observation,  questionaire  and documentation.  Analyzer  applied  is  validity  test,  reliability  test,  multiple  linear regression, test t, F test and coefficient of determination.    Based  on  result  of  analysis,  hence  inferential  :  1)  There  is  influence  between company  reputations,  loan  procedure  and  level  of  service  to  decision  of  consumer  in doing loan at KSU Jati Diri Simo Boyolali. 2) Loan procedure factor has influence that is most dominant to decision of consumer in doing loan at KSU Jati Diri Simo Boyolali. Based on the conclusion, hence can be suggested : Management KSU JATI DIRI SIMO BOYOLALI is expected to pays attention to factors influencing decision of consumer in doing loan for example reputation of company, loan procedure and level of service.